Ethical Outlook on Environmental Pollution (The Macau Ricci Institute Journal, 2020)
Air, water and soil pollution, along with waste disposal, is a growing issue of concern in modern societies. Increasingly, voices are emerging to call for incentives to curb the effects of mounting pollution. An estimate of 7.7 billion people was reported to populate the earth as of December 2019 (United Nations, 2019). In mid-July 2020 the world population clock set the world population at 7.8 billion. This population is tipped to increase to 9.7 billion by 2050, with a peak expected at 11 billion by 2100.